Débattre ou apprendre : faut-il choisir ? - Patrice Raynaud Serra (Éducation et Socialisation)
In between the consumption of culture, Humanitas, and the ideology where man is given once for all by the Humanists, this article attempts to find a median way where learn looks like debate and so escapes from all control provided by the knowing for the power. From the Platoon’s dialectical way that we found by a lecture of Hannah Arendt’s and Peter Sloterdijk’s writings, we search how to go back down into the cavern with an invisible term which opens debate.